QUALITY OF LIFE OF THE POPULATION OF LITHUANIA: THE CONCEPTION, DEVELOPMENT AND PROSPECTS - Rakauskienė, Ona Gražina; Lisauskaitė, Vaida (Ekonomika, 2009)
The article presents a thorough explanation of the concepts defining the well-being of life and proposes, on the basis of various authors’ research and trials, a generalised and complex understanding of the quality of life and a systemic concept of the quality of life. The article discusses the integrated indicators of the quality of life as used by international scientific and consulting institutions, methodologies and the taken measurements of the quality of life, presents international comparisons of indicators of the quality of life. On the basis of the system of indicators of the quality of life as offered by the authors, a change in the well-being of life of the Lithuanian population and its quality during the period of functioning of the market is analysed, and the principal positive and negative factors which affected the quality of life of the population in the period of 2000-2008 are identified. p>